DEVELOPMENT AND EVALUATION OF OSMOTICALLY CONTROLLED LOSARTAN POTASSIUM TABLETS FOR SUSTAINED RELEASE - Dhananjay Patil; Shivraj Jadhav; Chandrashkhar Patil; Sushant Ahire; Vaibhav Bhamare; Nilesh Chitte (The Bioscan, 2025)
The present study aimed to develop an osmotically controlled drug delivery system for Losartan potassium, a BCS Class I antihypertensive agent with a short half-life (1.5–2 hours), to achieve zero-order release and enhance therapeutic efficacy. Five formulations (LP1–LP5) were prepared by direct compression using HPMC K100M as the rate-controlling polymer and mannitol as the osmotic agent. Formulation development included core tablet compression followed by coating with a semi-permeable membrane and orifice drilling. Pre-compression parameters (bulk density, tapped density, Carr’s index, Hausner ratio) and post-compression characteristics (weight variation, hardness, friability, thickness, drug content, and in vitro release) were within acceptable limits. FTIR studies confirmed drug-excipient compatibility. In vitro dissolution studies in phosphate buffer (pH 6.8) demonstrated sustained drug release, with formulation LP3 showing the most promising profile—achieving 99.99% release over 12 hours and exhibiting near-zero-order kinetics. A 3-month stability study of LP3 confirmed its physical and chemical stability. Overall, a stable and effective osmotic drug delivery system for Losartan potassium was successfully developed, offering sustained release, reduced dosing frequency, and potential for improved patient compliance.